Media Attention for Climate Change Mitigation and Adaptation in Malaysia: A Comparative Analysis of Malaysia Chinese Newspaper Coverage - Rong, Cheong Jun; Zanuddin, Hasmah (Academic Research Publishing Group, 2018)
Climate change is a global problem and it is more likely caused by human activities and human greed. Studies on media representations of climate change by far are less potent on Asia country compared with Western societies. Climate change is one of the crucial issues and the media has been established to play an essential key role in constructing public awareness and policy adaptation. The research aims to examine and compare Malaysia's Chinese newspapers' portrayal on climate change mitigation and adaption from January 2015 to December 2015. Agenda setting theory is used to guide this study. Two major Chinese newspapers in Malaysia which are Sin Chew Daily and China Press were chosen as content analysis materials as both newspapers have the highest readership and circulation compare with others Chinese newspaper. Through the analysis of Malaysia major Chinese newspaper, both newspapers have a different level of media attention on climate change mitigation and adaptation issue. The media attention includes news monthly distribution, news focus, news perception, news genre and domesticity. Both newspapers mentioned above represented a unique way of reporting climate change issue. The greater of media attention on climate change issue can provide a wider exposure with the community.